INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PERUSAHAAN INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abednego Oematan, Ricky Imanuel; Radianto, Wirawan E.D. (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
This research was conducted to examine the effect of intellectualcapital on the company’s financial performance. The independent variablein this study is VAIC that developed by Pulic is used as a measure of intellectualcapital, while the dependent variable of this study is financial performancewhich is proxied by return on assets, return on equity, and assetturnover. The sample of this study is the infrastructure, utilities and transportationcompany listed on the Indonesia Stock Exchange (IDX) with theresearch period of 2014–2017. Data collection use purposive samplingmethod. The number of sample used in this study is 51 companies eachyear. This study uses multiple linear regression for data analysis. The resultsof this study indicate that VAIC as a measure of Intellectual capital has asignificant positive effect on return on assets, return on equity, and assetturnover. Overall, the results of this study indicate that contributing themost to the creation of added value and competitive advantage of the company.